How training quality, trainer competence, and satisfaction with training affect vocational identification of apprentices in vocational education programs - Wuttke, Eveline; Heinrichs, Karin; Koegler, Kristina; Just, Andreas (Frontiers in Psychology, 2024)
Vocational identification means being identified with an organization and with one's career. Both are key objectives of vocational education and training (VET) programs and advantageous for employees and employers. For employees, vocational identification is often associated with positive workrelated emotions and job satisfaction; for employers, workers' identification with the organization and the career enhances their performance and reduces turnover. Thus, investment in employees' professional development that has the potential to support vocational identification is advantageous for all involved. In light of current demographic changes and a decreasing demand for full-time work, which are leading to a shortage of skilled workers and lower enrolment in apprenticeship programs, it is essential to bind young talents to companies at an early stage and avoid resignations during or after training. Findings from various empirical studies confirm that those who identify with their chosen career and the organization for which they work are more satisfied, think less about quitting, and perform better.Little empirical research has been conducted on how apprentices in VET programs identify with their career or organization or the extent to which such identification enhances their job satisfaction. In this study, we therefore investigate factors that influence apprentices' identification with their career and organization, in particular, the effects of training quality and trainer competence.Our results indicate that apprentices identify strongly with their career and with the organization where they are doing their training and are mostly satisfied with the quality of their training. Structural equation modeling reveals the relevance of career choice, training quality, and job satisfaction for identification with an organization and (less) with a career. The learning and working conditions in the organization, and more specifically, the variety of tasks offered to the apprentices and the trainer's pedagogical aptitude explain satisfaction with the training and career identification; the trainer's presence and the apprentices' satisfaction with training explain, to some degree, variance in organizational identification.